Factors affecting male infertility - Pant, P. Raj (Journal of Institute of Medicine Nepal, 2010)
Introduction: Infertility is commonly defined as the failure of conception after at least 12 months of unprotected intercourse. 1 Accurate assessment of the prevalence of infertility has always been difficult because of the large scale population based studies. 2 Male factor is the only cause of infertility in about 20 % of infertile couples, but it may be a contributing factor in as many as 30 % to 40 % of cases.3 Factors like diabetes, bronchiectasis, high grade fever, long term medication, urinary tract infection, sexually transmitted infection, epididymitis, testicular injury, un-descended testis, mumps, orchitis, excessive alcohol, smoking, exposure to heat and certain chemicals effect in the spermatogenesis. Impotence or erectile dysfunction remains one of the important contributors in the male infertility. Methods: This is a prospective descriptive study conducted during the health camps in Sindhupalchowk, Manang, Baitedi, Rauthat and Darchula districts of the Nepal. The objective of the study is to find out the factors contributing to male infertility. Couples who were unable to conceive after regular, unprotected coitus of at least one year were included in the study. Detail history, clinical examination and semen analysis was done. Results: There was limited facility of investigation and treatment of infertility in the health camps. The diagnosis was based only on history, examination and semen analysis. Various factors like mumps, chemical exposure like men working in carpet factory, testicular trauma and smoking were found as contributing factor of male infertility in these districts. Conclusions: Testicular trauma, mumps, smoking is common in all the districts. Exposure to chemicals such as dyes, used in carpet factories seems to be responsible for infertility in some men of Sindhupalchowk and Darchula. Keywords: Azospermia; male infertility; oligospermia. DOI: 10.3126/joim.v31i3.2972 Journal of Institute of Medicine, December, 2009; 31(3) 10-12